Perspectives on Current Challenges and Opportunities for Bovine Viral Diarrhoea Virus Eradication in Australia and New Zealand - Reichel, Michael P. (Pathogens, 2018)
This review outlines the history of bovine viral diarrhoea virus (BVDV) and the current situation in Australia and New Zealand. BVDV has been reported as present in cattle from both countries for close to 60 years. It rates as the second most economically significant disease afflicting cattle, and is highly prevalent and spread throughout the beef and dairy industries. While other cattle diseases have been the subject of government control and eradication, infection with BVDV is presently not. Eradication has been undertaken in many other countries and been judged to be a good investment, resulting in positive economic returns. Presently, Australia and New Zealand have adopted a non-compulsory approach to control schemes, initiated and managed by farmers and veterinarians without the ultimate goal of eradication. Moving towards eradication is possible with the infrastructure both countries possess, but will require additional resources, coordination, and funding from stakeholders to move to full eradication.